Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1126/science.274.5295.2092
|View full text |Cite
|
Sign up to set email alerts
|

Reexpression of RAG-1 and RAG-2 Genes in Activated Mature Mouse B cells

Abstract: Recombination activating genes (RAG-1 and RAG-2), involved in V(D)J rearrangement of immunoglobulin genes, have been thought to be expressed only in immature stages of B-cell development. However, RAG-1 and RAG-2 transcripts were found to be reexpressed in mature mouse B cells after culture with interleukin-4 in association with several different co-stimuli. Reexpression was also detected in draining lymph nodes from immunized mice. RAG-1 and RAG-2 proteins could be detected by immunofluorescence microscopy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
184
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(197 citation statements)
references
References 26 publications
12
184
1
Order By: Relevance
“…These secondary rearrangements have indeed been described in a number of systems [43]. For example, it has been reported that RAG1 and RAG2 may be re-expressed in a subset of activated mature murine B cells population the GCs of draining lymph nodes [45], spleen and Peyer's patches [46]. A similar phenomenon has recently been reported to occur in human tonsillar B lymphocytes [47].…”
Section: The Primary and Secondary Repertoiresmentioning
confidence: 55%
“…These secondary rearrangements have indeed been described in a number of systems [43]. For example, it has been reported that RAG1 and RAG2 may be re-expressed in a subset of activated mature murine B cells population the GCs of draining lymph nodes [45], spleen and Peyer's patches [46]. A similar phenomenon has recently been reported to occur in human tonsillar B lymphocytes [47].…”
Section: The Primary and Secondary Repertoiresmentioning
confidence: 55%
“…RAG expression and L chain editing in the SPL have been reported earlier in immunized mice (67)(68)(69)(70)(71) and in LPS/IL-4-stimulated splenic B cells (72). However, such RAG expression and L chain editing may not occur, as initially thought, in mature splenic (germinal center) B cells.…”
Section: Rag Expression and L Chain Editing In B Cells Deficient For mentioning
confidence: 69%
“…[15][16][17][18][19][20] Recent studies proposed an interesting model in which mature B cells also undergo a similar process, termed receptor editing, in GCs of secondary lymphoid follicles after stimulation by Tdependent (TD) Ags. [21][22][23][24][25] This notion has been supported by the detection of rag1/rag2 transcripts and by the evidence of immunoglobulin gene rearrangements in situ, suggesting that receptor editing occurs in the GC light zone. 21 In addition, stimulation with anti-CD40 monoclonal antibody (mAb) plus interleukin-4 (IL-4), or lipopolysaccharide (LPS) plus IL-4, induced the up-regulation of rag1/rag2 transcripts and immunoglobulin gene rearrangements in mature surface immunoglobulin M (sIgM) ϩ B cells in vitro.…”
mentioning
confidence: 88%
“…Line 5 shows intermediate GFP signal, and line 7 shows a mixture of bright positive cells and cells with various levels of GFP signal during culture in the presence of IL-7. We also examined whether the same stimuli, reported previously by others, 22,[24][25][26] …”
mentioning
confidence: 91%